(untitled) (Texas Journal of Engineering and Technology, 2025)
This article examines modern technologies for the production, preparation, and quality control of concrete and reinforced concrete. The features of raw materials, technological stages of production of concrete mixtures, reinforcement, molding, and hardening of reinforced concrete structures are presented. Innovative methods for increasing the strength, durability, and crack resistance of structures through the use of chemical additives, modifying fillers, and composite reinforcement are analyzed.